Implementasi Kebijakan Pemerintah Kabupaten Kediri Dalam Pengolahan Limbah Industri Kecil (Studi pada Limbah Industri Kecil Tepung Tapioka di Desa Petok Kabupaten Kediri) - Fakhrirriza, Muhammad Afif (Jurnal Administrasi Publik, 2014)
Abstract: Policy Implementation of Kediri District Government in Treatment Small-Industrial Disposal (Study on Disposal of Small Tapioca Flour Industrial in Desa Petok Kabupaten Kediri). Some regulation have been by Kediri District Government in overcoming the impact industrial contamination of waste, among others is Local Regulation District of Kediri Number 7 Year 2008, Local Regulation District of Kediri Number 37 Year 2008, and Regulation Of Regent of Kediri Number 63 Year 2008. In implementing such programs would need a budget, executing actor, the target groups, as well as performance indicators. As for various attempts have been done by Kediri District Environmental Office addressed to small tapioca flour industrial in the Petok Village which includes disposal water treatment with IPAL technology, pemlengsengan Brantas River, the utilization of cassava / pulp for fattening cattle and manufacture of tapioca dryers. However, in reality a variety of pollution is often found in the surrounding community and environment small tapioca flour industry in the Petok village until now. Keywords : policy implementation, industrial disposal, Kabupaten Kediri Â  Ringkasan: Implementasi Kebijakan Pemerintah Kabupaten Kediri Dalam Pengolahan Limbah Industri Kecil (Studi Pada Limbah Industri Kecil Tepung Tapioka Di Desa Petok Kabupaten Kediri). Beberapa produk hukum telah dimiliki Kabupaten Kediri dalam mengatasi dampak pencemaran limbah industri, antara lain Peraturan Daerah Kabupaten Kediri Nomor 7 tahun 2008, Peraturan Daerah Kabupaten Kediri Nomor 37 Tahun 2008 dan Peraturan Bupati Kediri Nomor 63 Tahun 2008. Dalam mengimplementasikan program-program tersebut tentunya butuh anggaran, aktor pelaksana, target groups, serta indikator kinerja. Adapun upaya yang telah dilakukan Kantor Lingkungan Hidup Kabupaten Kediri terhadap industri kecil tepung tapioka di Desa Petok meliputi pengolahan limbah cair dengan teknologi IPAL, pemlengsengan Sungai Brantas, pemanfaatan onggok / ampas untuk penggemukan sapi, dan pembuatan alat pengering tapioka. Namun demikian, realitanya berbagai pencemaran masih sering ditemukan di masyarakat dan lingkungan sekitar industri kecil tepung tapioka di Desa Petok hingga kini. Â  Kata kunci: implementasi kebijakan, pencemaran limbah industri, Kabupaten Kediri